DNA Barcoding Ikan Kepala Timah Dan Betok Berdasarkan Gen COI sebagai Ikan Pioneer di Kolong Pascatambang Timah, Pulau Bangka - Diah Mustikasari; Rina Dwi Agustiani (Faculty of Science and Technology University Ibrahimy, 2021)
Tin mining activities in the Bangka Belitung Archipelago Province have led to the formation of pits that have not ideal water quality for aquatic organisms in general. Acidic pH and high metal contamination at certain age under certain causes only a few species are able to live well in these ecosystems. This study aimed to determine the identity of the pioneer fishes in ex-tin mining pit <1 year of Bangka Island through DNA barcoding based on COI gene. The pioneer fish in ex-tin mining pit <1 year were Kepala Timah fish dan Betok fish. Species determination was based on sequences similarity in NCBI and BOLD System showed that Ikan Kepala Timah had similarity with Aplocheilus panchax and its morphology indicated Ikan Kepala Timah was Aplocheilus panchax. The sequences similarity of Betok fish in NCBI and BOLD System showed that Betok fish had similarity with Anabas testudineusi and its morphology showed that Betok fish was Anabas testudineusi. The Kimua 2 Parameters (K-2P) Neighbour-Joining (NJ) clearly confirmed that Kepala Timah fish found in ex-tin mining pit <1 year was Aplocheilus panchax, whereas Betok fish was located outside clade of the group. It indicated that Betok fish was found in ex-tin mining pit <1 year can be expected as a morphotype of Anabas testudineusi that needed further confirmation in other studies, both molecularly and morphologically. The sequence data of COI gene of Betok fish found in ex-tin mining pit <1 year was expected can supported available sequence data of Anabas testudineusi in NCBI and BOLD System.